LITERASI DIGITAL, GURU, SEKOLAH DASAR, WILAYAH TERPENCIL, PENGABDIAN MASYARAKAT - Alip Alawi, Nurhidayat; Suwadah Rimang, Siti; Akib, Tasrif; Hardianto, Agus; Hafida (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
This community service activity aims to improve literacy competency to support technology-based learning. The methods used include training, interactive workshops, and direct mentoring. The results of the activity showed a significant increase in the understanding and digital skills of the participants. This article is digital literacy for elementary school teachers in remote areas. In the digital era, digital literacy is an important skill for educators to describe the implementation process, results, and impact of activities on improving the quality of education in the region. By providing structured training and mentoring, teachers can integrate digital technology into daily learning activities.